Early Sexual Experiences, Mental Health, and Risk Behavior among Black Non-Hispanic and Hispanic / Latino Men Who Have Sex with Men (MSM). Issue 1 (2nd January 2020) - Downing, Martin J.; Benoit, Ellen; Brown, Dominique; Coe, Lauren; Hirshfield, Sabina; Pansulla, Louis; Carballo-Diéguez, Alex
ABSTRACT: Black and Latino men who have sex with men (MSM) are disproportionately affected by childhood sexual abuse (CSA). Investigating these histories is often confounded by underreporting and varied definitions of abuse. Unrecognized abuse may manifest in unhealthy ways, specifically psychological distress, substance use, and high-risk sexual behaviors. Black and Hispanic/Latino MSM in New York City discussed formative sexual experiences in in-person interviews. Eligible men reported a sexual experience occurring before age 16 with a man or woman 18 or older at the time. Among interviewees ( n = 61), men living with HIV were significantly younger at the time of their first sexual experience with a male partner compared to HIV-negative men. Approximately half of interviewees (47.5%) scored at or above the diagnostic cutoff for post-traumatic stress disorder (PTSD). Hispanic/Latino men had increased odds of scoring at or above the diagnostic cutoff for PTSD compared to Black non-Hispanic men. Further, nearly half of interviewees (46%) scored at or above the diagnostic cutoff for harmful drug use or possible drug dependence. Study findings have implications for future research using an indirect approach to uncovering potential sexual abuse during childhood, and associations with adult health outcomes.